Pengembangan Objek Wisata Puncak Pela sebagai Upaya Peningkatan Potensi Pariwisata Nagari Lawang Mandahiling - Yen Fitriana; Ikhsan Devid; Sufi Anugrah (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2026)
Village tourism is a strategic sector in promoting community economic growth through the utilization of natural potential and local wisdom. Nagari Lawang Mandahiling, Salimpaung District, Tanah Datar Regency, has natural tourism potential in the form of Puncak Pela, which offers hilly landscapes with views of Mount Marapi and Mount Sago. However, this potential has not been optimally managed due to limited facilities, infrastructure, accessibility, and low community awareness of tourism development. This community service activity aims to support the development of the Puncak Pela tourist attraction through improving accessibility, organizing trekking routes, and strengthening the identity of the tourism area based on community participation. The methods used include field observation, participatory approaches, SWOT analysis, and the development of tourism facilities and infrastructure. The results indicate improvements in accessibility, safety, and tourist attractiveness through the opening and cleaning of trekking routes, installation of directional signboards, and the inauguration of the trekking route. Thus, Puncak Pela has the potential to be developed as a leading nature-based tourism destination that supports tourism development and enhances the local economy of Nagari Lawang Mandahiling.